Descriptions of larvae of Megadytes (Coleoptera: Dytiscidae: Dytiscinae): The subgenera Trifurcitus and Megadytes s. str., ground plan of chaetotaxy of the genus and phylogenetic analysis - Michat, Mariano Cruz (2010)
The three larval instars of Megadytes (M.) carcharias Griffini and M. (Trifurcitus) fallax (Aubé) are described and illustrated in detail for the first time, with an emphasis on morphometry and chaetotaxy of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. The ground plan of chaetotaxy of the genus Megadytes Sharp is described and illustrated based on three of the four recognised subgenera. First-instar larvae of Megadytes are characterised by the presence of a large number of additional sensilla on almost every part of the body. Primary chaetotaxy of the subgenera (Bifurcitus Brinck based on third instar) is very similar, with few differences including (1) shape of the setae on the anterior margin of the frontoclypeus; (2) presence or absence of a ring of multi-branched setae on distal third of mandible; and (3) number of setae on the urogomphus. A cladistic analysis of Dytiscidae, based on 169 larval characters and 34 taxa, indicates that: (1) Trifurcitus Brinck deserves generic status; (2) Cybistrini are not closely related to Hydroporinae; (3) the absence of a galea in Cybistrini is a secondary loss independent of that in Hydroporinae; (4) Cybistrini are well supported by many characters (including several aspects of first-instar chaetotaxy).